Lactarius battagramensis (Russulales, Basidiomycota) and its ectomycorrhizal association in temperate forests of Khyber Pakhtunkhwa, Pakistan - Khan, Muhammad Binyamin; Sana; Naseer, Arooj; Ishaq, Muhammad; Kiran, Munazza; Tarafder, Entaj; Fiaz, Muhammad; Khalid, Abdul Nasir; Wen, Ting Chi (Phytotaxa, 2025)
This article introduces Lactarius battagramensis as a novel species along with its ectomycorrhizal association from the temperate forests of Pakistan. Morpho-anatomical data coupled with sequence analyses and phylogeny inference of nrDNA ITS sequences are obtained from fruit bodies and ectomycorrhiza, leading to a better circumscription of new species. This new species is characterized by pale cream to vivid yellow and plano-concave to concave pileus, adnate lamellae that are concolorous to pileus, stipe that is tapering towards base, globose to broadly ellipsoid basidiospores forming partial to nearly complete reticulum, fusiform hymenial macrocystidia, absence of hymenial pseudocystidia, narrowly clavate paracystidia, and a hypoepithelium pileipellis. Phylogenetic estimation based on sequences from the internal transcribed spacer (ITS) region of the nuclear ribosomal DNA (nrDNA) genes inferred that L. battagramensis formed a separate and distinct clade sister to L. mediterraneensis with a strong support value, which represents the uniqueness of this species from other species of L. subgen. Lactarius.